AKTIVITAS FISIK RUTIN SEBAGAI MODULATOR SENSITIVITAS INSULIN PADA OBESITAS - Dian Syafitri; Khairun Nisa Berawi; Ahmad Arkan Ichsan (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
Obesity is a state of abnormal or excessive fat accumulation in the adipose tissue of the body that could potentially cause the health problems. The prevalence of obesity increases every year in Indonesia. Based on the Basic Health Research (RisKesDas) 2018, Indonesian obesity incidences ranked 18, 8% in 2007, increased to 26, 6% in 2013 and topping 31, 0% in 2018. The increase of obesity prevalence is directly proportional to comorbid conditions. Insulin insensitivity is seen in obese patients, and may lead to insulin resistance. This correlates with a disrupted glucose absorption rate, which is induced by insulin. Glucose molecules could not enter the cell and could not be utilized by the cells, as a result there is an n increase in blood glucose levels. Conditions with abnormally high glucose levels is called hyperglycemia. Hyperglycemia can lead into a variety chronic diseases, like diabetes mellitus. One of the straightforward, cost-effective and efficacious therapy strategies that can be executed to overcome obesity and increase the insulin sensitivity is through increased physical activity. Categories of physical activity are divided between sedentary, light, moderate, vigorous, and high, where each category has varying energy demands. Physical activity that is carried out consistently and routinely may further reduce body weight, as well as maintain proportional body weight in the long run and further increase insulin sensitivity, and reduce the risk chronic disease like diabetes mellitus.